2003
DOI: 10.1016/s0928-8244(03)00229-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation byYersinia enterocolitica: comparison of live and heat-killed bacteria

Abstract: This study compared the immunomodulating properties of viable and killed Yersinia enterocolitica O9 in BALB/c mice. At 10 days after infection by the intragastric route, ex vivo assays showed a suppression of spleen cell proliferation in response to Salmonella lipopolysaccharide, concanavalin A and heat-killed yersiniae. Mice infected with Y. enterocolitica O9 for 10 days resisted the challenge with a lethal dose of Listeria monocytogenes. In contrast, intravenous administration of heat-killed yersiniae did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Generally, most of the live bacteria are existed in the form of liquid or suspension, which may lead to the difficulties of reserving and processing. In addition, compared with the live or formalin‐killed bacteria on immune hosts, the heat‐killed Yersinia enterocolitica retain interesting immunomodulating properties on mice (Ruiz‐Bravo, Bujalance, Romero, Moreno & Jimenez‐Valera ), and heat‐killed bacterins of Vibrio vulnificus induced a better antibody response than that induced by formalinised bacterins in flounder, Paralichthys olivaceus (Park, Park & Jeong ). Heat‐killed Lactobacillus plantarum L‐37 (HK L‐137) was acquired by heat‐treating Lactobacillus plantarum , which had been used as an immunostimulants to induce interleukin‐12 production and antitumor effect in mice, to enhance gamma interferon production and to stimulate a substance that suppresses virus reproduction and other T‐cells and activates macrophages cells (Murosaki, Yamamoto, Ito, Inokuchi, Kusaka, Ikeda & Yoshikai ; Murosaki, Muroyama, Yamamoto & Yoshikai ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, most of the live bacteria are existed in the form of liquid or suspension, which may lead to the difficulties of reserving and processing. In addition, compared with the live or formalin‐killed bacteria on immune hosts, the heat‐killed Yersinia enterocolitica retain interesting immunomodulating properties on mice (Ruiz‐Bravo, Bujalance, Romero, Moreno & Jimenez‐Valera ), and heat‐killed bacterins of Vibrio vulnificus induced a better antibody response than that induced by formalinised bacterins in flounder, Paralichthys olivaceus (Park, Park & Jeong ). Heat‐killed Lactobacillus plantarum L‐37 (HK L‐137) was acquired by heat‐treating Lactobacillus plantarum , which had been used as an immunostimulants to induce interleukin‐12 production and antitumor effect in mice, to enhance gamma interferon production and to stimulate a substance that suppresses virus reproduction and other T‐cells and activates macrophages cells (Murosaki, Yamamoto, Ito, Inokuchi, Kusaka, Ikeda & Yoshikai ; Murosaki, Muroyama, Yamamoto & Yoshikai ).…”
Section: Introductionmentioning
confidence: 99%
“…In coculture models where pathogen viability is a consideration, preserving microbial cell structure is best addressed by the use of gamma-irradiation to inactivate the microbial cells [81]. This represents a better alternative to heat killing or UV irradiation, since both techniques denature microbial cell structures that may be important for host cell interactions [82, 83]. Whilst all of these approaches compromise the advantages of a viable pathogen in coculture, they do provide modelling conditions not possible with the use of viable microbes where microbial overgrowth occurs.…”
Section: Benefits and Limitations Of Epithelial Cell Coculturementioning
confidence: 99%
“…In addition, a comparison of effects of heat‐killed bacteria with live or formalin‐killed bacteria on immune hosts was conducted. The comparison showed that heat‐killed Yersinia enterocolitica retain interesting immunomodulating properties on mice (Ruiz‐Bravo et al 2003), and heat‐killed bacterins of V. vulnificus induced a better antibody response than that induced by formalinised bacterins in flounder, P. olivaceus (Park et al 2001).…”
mentioning
confidence: 99%